Back in the Republic of Conscience: Seamus Heaney's The Cure at Troy, its politics, ethics and aesthetics. Issue 4 (7th June 2017) - Parker, Michael
ABSTRACT: For Seamus Heaney translation was by no means peripheral to his literary project, but central to it, not least as a means of renewing his creative impetus and extending the reach of his work across multiple times and cultures. This essay examines the reasons behind Heaney's increasing immersion in Greek literature from the mid-1980s onwards. It examines how the political and ethical issues Sophocles addresses in Philoctetes drew him to the play, and identifies the contexts – international and local – which shaped The Cure at Troy 's composition and reception. Unlike many previous discussions which dwell primarily on material Heaney added to the original, this essay offers a meticulous analysis of the entire Cure . It evaluates the quality of its poetry and its relationship to Heaney's lyric work up to 1990 and after. A recurring focus of interest are those moments and extended passages where Heaney takes greatest pains to make the source text his own, to settle in and 'colonize' it. In demonstrating where, when and why divergences occur, his version is repeatedly compared and contrasted with those of four other eminent translators. What emerges from this is how fully he sought to re-imagine the characters and recast the Chorus, ensuring the audience's empathy for and engagement with these flawed specimens of humanity.